-4+2p=-9+2p+s

Simple and best practice solution for -4+2p=-9+2p+s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+2p=-9+2p+s equation:


Simplifying
-4 + 2p = -9 + 2p + s

Add '-2p' to each side of the equation.
-4 + 2p + -2p = -9 + 2p + -2p + s

Combine like terms: 2p + -2p = 0
-4 + 0 = -9 + 2p + -2p + s
-4 = -9 + 2p + -2p + s

Combine like terms: 2p + -2p = 0
-4 = -9 + 0 + s
-4 = -9 + s

Solving
-4 = -9 + s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-1s' to each side of the equation.
-4 + -1s = -9 + s + -1s

Combine like terms: s + -1s = 0
-4 + -1s = -9 + 0
-4 + -1s = -9

Add '4' to each side of the equation.
-4 + 4 + -1s = -9 + 4

Combine like terms: -4 + 4 = 0
0 + -1s = -9 + 4
-1s = -9 + 4

Combine like terms: -9 + 4 = -5
-1s = -5

Divide each side by '-1'.
s = 5

Simplifying
s = 5

See similar equations:

| -11+4n=5n-(11+17) | | 5+4(-3-6x)=35-3x | | -8k+s=-7k-1 | | 35=.5*h(4+3) | | -2s-2=-6s+6+4s | | 5(a-3)+2=3a-19 | | -7b-6=-6-7b | | 2c=3(j+m) | | 5-2x+2=12 | | 7y+4(y-6)=5(y+2)-5 | | 4x-2y=20 | | -0.2(-4p+4)-1.2p= | | x^2+10x-5=0 | | -5(2x+9)+5= | | 9(x+3)=3(3x+3)+18 | | m+7.3=6.1 | | -4x+38=-7(-3+3x) | | 5-2(x+2)=12 | | (x+2)+7=(2+x)+7 | | 9=-3-6n+2n | | 4x+5=-5+2x+20 | | 7x-1=3y+8 | | 17=7x+10 | | 0=-x^2+10x-25 | | 5ax-6=3x-c | | n^2=0-7 | | 5+2(x-1)=12 | | x^2=10x-25 | | -5+5v=7(8-8v) | | 3(x-1)=2x-y | | -5(2p+4)-46=4(4p+3) | | y-5.7=3.6 |

Equations solver categories